Targeted inhibition of ferroptosis in bone marrow mesenchymal stem cells by engineered exosomes alleviates bone loss in smoking-related osteoporosis - Yao Wang; Lin Sun; Zhenglin Dong; Tianyu Zhang; Leining Wang; Yihui Cao; Hui Xu; Chenglei Liu; Bo Chen (Materials Today Bio)
Smoking-related osteoporosis (SROP) is characterized by reduced bone mass, primarily due to the accumulation of tobacco-derived toxins. This study demonstrates the activation of ferroptosis and reactive oxygen species (ROS)-related pathways in the bone marrow mesenchymal stem cells (BMSCs) of SROP mice. Here, we integrated genetic engineering and bone-targeting peptide modification to develop innovative bone-targeting engineered exosomes. Using genetic engineering techniques, we introduced α-1,3-fucosyltransferase 6 (Fut6), a key protein involved in prostate cancer bone metastasis, and identified exosomes expressing Fut6 (F6-exo) with bone-targeting capabilities. Additionally, we modified these exosomes with a bone-targeting peptide, (AspSerSer)6, to synthesize F6-(DSS)6-exo. F6-(DSS)6-exo enabled the targeted delivery of curcumin, restoring the osteogenic differentiation potential of BMSCs and mitigating bone loss in SROP mouse models. In summary, this study highlights the combination of genetic engineering and hydrophobic diacylglycerol insertion as a novel targeted therapeutic approach for SROP.